Formal concept analysis with negative attributes for forgery detection. Issue 6 (30th September 2020) - Ojeda‐Aciego, Manuel; Rodriguez‐Jimenez, José Manuel
Abstract : Europe's system of open frontiers, commonly known as "Schengen, " let people from different countries travel and cross the inner frontiers without problems. Different documents from these countries, not only European, can be found in road checkpoints and there is no international database to help Police forces to detect whether they are false or not. People who need a driver license to access to specific jobs, or a new identity because of legal problems, often contact forgers who provide false documents with different levels of authenticity. Governments and Police Forces should improve their methodologies, by ensuring that staff is increasingly better able to detect false or falsified documents through their examination, and follow patterns to detect and situate these forgers. In this work, we propose a method, based in formal concept analysis using negative attributes, which allows Police forces analyzing false documents and provides a guide to enforce the detection of forgers.